Modeling the Electrostatic Actuation of Nanomechanical Pillar Dimers - Kainz, Andreas; Beigelbeck, Roman; Schmid, Silvan (Frontiers in Mechanical Engineering, 2021)
With their unparalleled mass sensitivity, enabling single-molecule mass spectrometry, nanomechanical resonators have the potential to considerably improve existing sensor technology. Vertical pillar resonators are a promising alternative to the existing lateral resonator designs. However, one major obstacle still stands in the way of their practical use: The efficient transduction (actuation & detection) of the vibrational motion of such tiny structures, even more so when large arrays of such nanopillars need to be driven. While electrostatic forces are typically weak and, on the nanoscale even weaker, it is worth revisiting the possibility of electrostatic actuation of nanomechanical pillars and other nanomechanical structures. In this paper, these forces produced by an external field are studied both analytically and numerically, and their dependencies on the geometric dimensions are discussed. Furthermore, the expected deflections for different configurations of pillar geometries are calculated and compared.